Comparative experimental anesthesia efficacy study of epidural injection at the sacrococcygeal space using ultrasound guidance versus blindness technique in Egyptian donkeys (Equus asinus) - Mohamed A. Hamed; Hazem Hamouda; Mohammed Elmetwally; Foad Farrag; Mohamed Abdo Rizk; Mohamed M. A. Abumandour; Yamen Mohammed Hegazy; Alaa Samy (BMC Veterinary Research)
Abstract The study investigates the effectiveness of blind and ultrasound-guided epidural injections in Egyptian donkeys in the sacrococcygeal region, a topic of limited research, by comparing and assessing their onset in 20 healthy adult donkeys of both sexes. In the first group, we used ten cadaver donkeys that were humanely euthanized. In the second group, we used 10 live, healthy adult donkeys to assess the efficacy and time of analgesia onset for blind and ultrasound-guided epidural injections at the sacrococcygeal region. Cadavers were randomly designated to blind (n = 5) or US-guided (n = 5) epidural injections at the sacrococcygeal region in sternal recumbency in donkeys using Methylene Blue (1%) as a diagnostic marker for caudal epidural injection. The injection criteria were comparatively assessed between the two techniques of injection. Our findings comparing the blind and US-guided injection approaches showed substantially higher needle accuracy penetration to comparatively assess these two injection techniques. Both injection difficulties and trial numbers were significantly greater in blind techniques as opposed to US-guided procedures. US-guided injection procedures revealed the effectiveness of the time needed for perfect placement of the needle was significantly less than with a blind one. A shorter time for the onset of analgesia was achieved with the ultrasound-guided method, although the difference was not statistically significant (P < 0.09). In conclusion, the ultrasound-guided technique of the epidural injection provided a number of benefits over the blind one, including the capacity to directly view the needle and distribute local anesthetic and avoid unintentional vascular damage, in comparison with traditional blind techniques. Our study aims to enhance the accuracy and safety of epidural anesthesia injection at the sacrococcygeal space in Egyptian donkeys using ultrasound guidance in the veterinary surgical field.